Effect of pretreatment on the enzymatic hydrolysis of kitchen waste for xanthan production. (January 2017) - Li, Panyu; Zeng, Yu; Xie, Yi; Li, Xiang; Kang, Yan; Wang, Yabo; Xie, Tonghui; Zhang, Yongkui
Highlights: Effect of pretreatment on enzymatic hydrolysis of KW was systematically studied. Kinetic analysis was employed for describing the effect of pretreatment. Diluted acid pretreatment was favorable for the overall hydrolysis process. Concentration of reducing sugar and KDN reached 51.87 g/L and 7.79 g/L, respectively. KW was used as the raw material for xanthan fermentation. Abstract: The study was carried out to gain insight into the effect of pretreatment on enzymatic hydrolysis of kitchen waste (KW) for xanthan fermentation. Herein, various pretreatments were applied and it was found that chemical pretreatment had positive effect on the following enzymatic or overall hydrolysis process. The highest reducing sugar concentration was obtained as 51.87 g/L from 2% HCl (90 °C) pretreated sample, while the Kjeldahl nitrogen (KDN) concentration was 7.79 g/L. Kinetic study showed that first order kinetic model was suitable to describe the enzymatic hydrolysis process. The obtained kitchen waste hydrolysate (KWH) was successfully applied for xanthan fermentation. Xanthan concentration reached 4.09–6.46 g/L when KWH with 2% HCl (90 °C) pretreatment was applied as medium. In comparison, a xanthan concentration of 3.25–5.57 g/L was obtained from KWH without pretreatment. Therefore, pretreatment of KW using diluted acid is favorable for the overall hydrolysis process and effective for xanthan fermentation.